Long-term condition management for prisoners: improving the processes between community and prison - NMJ Wright (BMC Family Practice, 2021)
Abstract Background Prisoner populations have a disproportionately high prevalence of risk factors for long-term conditions (LTCs), and movement between community and prisons is a period of potential disruption in the ongoing monitoring and management of LTCs. Method Nineteen qualitative interviews with staff, recruited by purposive sampling for professional background, were conducted to explore facilitators and barriers to screening, monitoring and medicines management for LTCs. Results There is variability in prisoner behaviours regarding bringing community GP-prescribed medication to prison following arrest and detention in police custody, which affects service ability regarding seamless continuation of community prescribing actions. Systems for actively inputting clinical data into existing, nationally agreed, electronic record templates for QOF monitoring are under-developed in prisons and such activity is dependent upon individual “enthusiast(s)”. Conclusion There is a pressing need to embed standardised QOF monitoring systems within an integrated community/prison commissioning framework, supported by connectivity between prison and community primary care records, including all activity related to QOF compliance.